O comportamento sedentário e a adiposidade se associam com os níveis de testosterona de meninos pós-púberes com excesso de peso? - Oliveira Júnior, Júlio Duarte de (2019)
INTRODUCTION: Some lifestyle factors, such as adiposity, are negatively related to testosterone levels, however it is not clear whether sedentary behavior, especially in overweight post-pubertal boys, can also be a factor influencing testosterone levels, which is related to important functions in the process of growth and development. OBJECTIVE: To verify the association between the sedentary behavior and adiposity with the salivary testosterone levels of post-pubertal boys with overweight and obesity. METHODS: A descriptive research, with an observational technique and a cross-sectional design. Twenty-nine obese boys (16,5±1,1 years old; 30,1±3,5 kg/m2 ), without comorbidities and that reached the age of peak height velocity were included in this analysis. Somatic maturation was used to classify the subjects regarding the peak height velocity. Salivary testosterone levels were assessed by enzyme-linked immunosorbent assay (ELISA). The sedentary behavior was evaluated by triaxial accelerometer (ActiGraph GT3X+) over seven consecutive days. Adiposity was measured by X-ray absorptiometry (DXA). A simple linear regression was used to verify the association between the independents variables (sedentary behavior and adiposity) in an isolated manner on the testosterone levels. A multivariate linear regression model was used to verify if the sedentary behavior and adiposity are jointly associated with the testosterone levels. A value of p <0.05 was used for statistical significance. RESULTS: It was verified that there isn't statistically significant association between the sedentary behavior with the salivary testosterone levels [F (1,27) = 0,171; p = 0,68]. On the other hand, the adiposity [F(1;27) = 6,647; p = 0,01] was statistically significant to explain the hormonal levels. In addition, in the joint analysis, it was found that there was no association between sedentary behavior and testosterone levels (T = 0.257; p = 0.80), while body fat was negatively associated with testosterone levels (T = -2.506; p = 0.01). CONCLUSION: Sedentary behavior was not associated with salivary testosterone levels in post-pubertal obese boys. On the other hand, testosterone levels were negatively associated with the degree of adiposity.